2009
DOI: 10.1155/2009/175216
|View full text |Cite
|
Sign up to set email alerts
|

The Use of N-Terminal-Pro-BNP in Preterm Infants

Abstract: The use of natriuretic peptides in the neonatal population is emerging. B-type Natriuretic Peptide (BNP) and N-terminal-Pro-BNP (NTpBNP) are used in the adult population to assess myocardial function and volume loading. Their role in prognosis following cardiac surgery has also been identified. In preterm infants NTpBNP is becoming increasingly recognised as a potential screening tool for patent ductus arteriosus (PDA), and a marker for myocardial performance. In addition, NTpBNP may provide prognostic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
0
18
0
8
Order By: Relevance
“…In another study by S. Mannarino et al the amount of BNP was tested in the umbilical cord of term and preterm infants. Also a greater increase was observed in BNP level of preterm infants in comparison with the term cases (25). In another study, Remzi Kardag et al demonstrated relationships between intracellular pressure and natriuretic peptide, in the plasma of patients with hypothyroidism conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In another study by S. Mannarino et al the amount of BNP was tested in the umbilical cord of term and preterm infants. Also a greater increase was observed in BNP level of preterm infants in comparison with the term cases (25). In another study, Remzi Kardag et al demonstrated relationships between intracellular pressure and natriuretic peptide, in the plasma of patients with hypothyroidism conditions.…”
Section: Discussionmentioning
confidence: 89%
“…In a study by Gustavo Rocha et al there was a relationship between BNP serum levels in premature infants with respiratory distress syndrome (RDS) (25). In another study by Joseph et al increase in BNP serum level was demonstrated as a marker for recognition of BPD in prematurity.…”
Section: Discussionmentioning
confidence: 97%
“…BNP levels have also been shown to transiently increase in preeclampsia, with normalization after delivery [10]. In children, BNP levels have been studied in the setting of congenital heart disease [3] and patent ductus arteriosus (PDA) [11], as well as persistent pulmonary hypertension of the newborn (PPHN) [4]. Serum BNP levels are significantly increased in patients with hemodynamically symptomatic PDA requiring indomethacin administration and/or surgical ligation compared to those with asymptomatic PDA [12].…”
Section: Discussionmentioning
confidence: 99%
“…ElKhuffash et al (5) reported that BNP level was affected by PDA diameter and LA/Ao ratio after the 12 th hour after birth and with the increase in both of these values BNP increased significantly in the review they published about BNP in preterm babies. These results in the literature are compatible with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Brain natriuretic peptide is a polypeptide consisting of 32 amino acids and a hormone released from the ventricles of the heart in case of hemodynamic stress and congestive heart failure (4)(5)(6). BNP which is released from the ventricles as a response to increased ventricular volume load is a cardiac marker which is convenient for use for urgent diagnosis, since it is produced rapidly at high levels in cases of congestive heart failure, left ventricular dysfunction and increase of pressure and volume load in the left and right ventricles.…”
Section: Introductionmentioning
confidence: 99%